Formation and Trend of Guanxi Practice and Guanxi Phenomenon - Jiang, Guoping; Lo, T. Wing; Garris, Christopher P. (International Journal of Criminology and Sociology, 2012)
With the increase of interactions between Chinese and international communities, guanxi, a Chinese term, has catching more and more attentions from non-Chinese speaking people. Guanxi, from a sociological perspective, is formed on the ascribed, social or third party bases through the mechanism of ganqing and renqing. Different from other scholars, the authors consider guanxi phenomenon is an outcome of co-impacts from Confucianism and institutionalization of material factors and structural factors. It is argued that guanxi phenomenon will decline in future China gradually because of rationalization required by capitalism but will not disappear completely due to human nature and cultural nature.